O pewnych aspektach intertekstualizacji proprialnej w świetle najnowszych badań - Hrynkiewicz-Adamskich, Bożena (Studia Rossica Posnaniensia, 2016)
A new perspective in research on proper names has appeared recently. A proper name is now treated as a text unit. The article discusses intertextual relations between different classes of onyms and some extralinguistic aspects of proprial intertextualisation.